2005
DOI: 10.1557/proc-866-v3.1
|View full text |Cite
|
Sign up to set email alerts
|

GaN:Eu Interrupted Growth Epitaxy (IGE): Thin Film Growth and Electroluminescent Devices

Abstract: The GaN:RE phosphor development plays a major role in the GaN:RE AC thick dielectric electroluminescent (TDEL) device optimization. In this paper we report on EL devices fabricated using Eu-doped GaN red phosphors films grown by interrupted growth epitaxy (IGE). IGE consists of a sequence of ON/OFF cycles of the Ga and Eu beams, while the N 2 plasma is kept constant during the entire growth time. IGE growth of GaN:Eu resulted in significant enhancement in the Eu emission intensity based primarily at 620.5nm. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…% at ϳ70 nm depth. A second set of samples ͑Table II͒ was grown by MBE with the interrupted growth epitaxy ͑IGE͒ technique, 19,20 for which the shutters of group III elements ͑Ga and Eu͒ are open ͑"on"͒ for a part of the cycle and close ͑"off"͒ for the rest of the time. The group V is on throughout the entire IGE cycling time.…”
Section: Samples and Measurementsmentioning
confidence: 99%
“…% at ϳ70 nm depth. A second set of samples ͑Table II͒ was grown by MBE with the interrupted growth epitaxy ͑IGE͒ technique, 19,20 for which the shutters of group III elements ͑Ga and Eu͒ are open ͑"on"͒ for a part of the cycle and close ͑"off"͒ for the rest of the time. The group V is on throughout the entire IGE cycling time.…”
Section: Samples and Measurementsmentioning
confidence: 99%
“…It means that high quality crystal can be obtained, but LED operation was not achieved. MBE growth conditions not only affect the emission capability [18], but also the emission wavelength corresponding to Eu, i.e., the different local arrangements around Eu atoms [19]. Moreover, Okada et al reported that PL peak from Eu-ion changed by Mg co-doping [20].…”
Section: Introductionmentioning
confidence: 99%
“…10 Most of the mechanisms investigations were carried out on samples grown using molecular beam epitaxy ͑MBE͒. In addition, luminescence studies of GaN:Eu grown by interrupted growth epitaxy [11][12][13] ͑IGE͒ and Eu-implanted GaN ͑Ref. 14͒ have been reported.…”
mentioning
confidence: 99%